IMPACT OF THE COVID-19 PANDEMIC ON VEGETABLE BUSINESS INCOME IN PATTINOANG VILLAGE, GALESONG DISTRICT TAKALAR DISTRICT - Andi Gujong Rusli Gujong (Institute of Computer Science (IOCS), 2022)
This study aims to determine the impact of covid-19 on the income of vegetable farmers before and during the pandemic in Pattinoang Village, Galesong District, Takalar Regency and to find out the difference in the income of vegetable farmers before and during the covid-19 pandemic in Pattinoang Village, Galesong District, Takalar Regency. Sampling in the study was done by simple random sampling technique as many as 15 vegetable farmers from a total population of 103 farmers. The data analysis used is the analysis of production and income as well as the analysis of the t-test (Paired Test). The result showed that the impact of the covid-19 pandemic on the income of vegetable farmers in Pattinoang Village, Galesong District, Takalar Regency decreased. This happens because the costs used in vegetable farming increase while the price of vegetables decreases which result in decreased revenues. Thus, the average income of vegetable farmers before the covid-19 pandemic was IDR 935,495.00 and decreased during the covid-19 pandemic to IDR 729,213.00.